The EUMETNET AutoPollen programme: establishing a prototype automatic pollen monitoring network in Europe - Bernard Clot; Stefan Gilge; Lenka Hajkova; Donát Magyar; Helfried Scheifinger; Mikhail Sofiev; Fabienne Bütler; Fiona Tummon (Aerobiologia, 2024)
Operational pollen monitoring networks have developed across Europe, and the world more generally, in response to the increasing prevalence of pollen allergy and asthma. Routine pollen observations are in large part currently still based on time-intensive manual techniques developed in the 1950s. These methods suffer from low temporal resolution and long delays in data availability. Recent technological developments are revolutionising the field making real-time high-temporal resolution measurements possible. This paper describes the rationale behind the EUMETNET AutoPollen programme, which aims to develop a prototype automatic pollen monitoring network across Europe. We provide a brief description of the current state-of-the-art, then an overview of new technologies, and finally the main tasks of the AutoPollen programme.

Past and future impacts of land-use changes on ecosystem services in Austria - Uta Schirpke; Erich Tasser; Stefan Borsky; Martin Braun; Josef Eitzinger; Veronika Gaube; Michael Getzner; Stephan Glatzel; Thomas Gschwantner; Mathias Kirchner; Georg Leitinger; Bano Mehdi-Schulz; et al. (Journal of Environmental Management, 2023)

Climate change fingerprints in recent European plant phenology - Annette Menzel; Ye Yuan; Michael Matiu; Tim Sparks; Helfried Scheifinger; Regula Gehrig; Nicole Estrella (Global Change Biology, 2020)
A paper published in Global Change Biology in 2006 revealed that phenological responses in 1971–2000 matched the warming pattern in Europe, but a lack of chilling and adaptation in farming may have reversed these findings. Therefore, for 1951–2018 in a corresponding data set, we determined changes as linear trends and analysed their variation by plant traits/groups, across season and time as well as their attribution to warming following IPCC methodology. Although spring and summer phases in wild plants advanced less (maximum advances in 1978–2007), more (~90%) and more significant (~60%) negative trends were present, being stronger in early spring, at higher elevations, but smaller for nonwoody insect‐pollinated species. These trends were strongly attributable to winter and spring warming. Findings for crop spring phases were similar, but were less pronounced. There were clearer and attributable signs for a delayed senescence in response to winter and spring warming. These changes resulted in a longer growing season, but a constant generative period in wild plants and a shortened one in agricultural crops. Phenology determined by farmers’ decisions differed noticeably from the purely climatic driven phases with smaller percentages of advancing (~75%) trends, but farmers’ spring activities were the only group with reinforced advancement, suggesting adaptation. Trends in farmers’ spring and summer activities were very likely/likely associated with the warming pattern. In contrast, the advance in autumn farming phases was significantly associated with below average summer warming. Thus, under ongoing climate change with decreased chilling the advancing phenology in spring and summer is still attributable to warming; even the farmers’ activities in these seasons mirror, to a lesser extent, the warming. Our findings point to adaptation to climate change in agriculture and reveal diverse implications for terrestrial ecosystems; the strong attribution supports the necessary mediation of warming impacts to the general public.

Pan European Phenological database (PEP725): a single point of access for European data - Barbara Templ; Elisabeth Koch; Kjell Bolmgren; Markus Ungersböck; Anita Paul; Helfried Scheifinger; This Rutishauser; Montserrat Busto; Frank-M. Chmielewski; Lenka Hájková; Sabina Hodzić; Frank Kaspar; et al. (International Journal of Biometeorology, 2018)

Deuterium excess in precipitation of Alpine regions – moisture recycling - Klaus Froehlich; Martin Kralik; Wolfgang Papesch; Dieter Rank; Helfried Scheifinger; Willibald Stichler (Isotopes in Environmental and Health Studies, 2008)

European phenological response to climate change matches the warming pattern - ANNETTE MENZEL; TIM H. SPARKS; NICOLE ESTRELLA; ELISABETH KOCH; ANTO AASA; REIN AHAS; KERSTIN ALM‐KÜBLER; PETER BISSOLLI; OL'GA BRASLAVSKÁ; AGRITA BRIEDE; FRANK M. CHMIELEWSKI; ZALIKA CREPINSEK; et al. (Global Change Biology, 2006)
Global climate change impacts can already be tracked in many physical and biological systems; in particular, terrestrial ecosystems provide a consistent picture of observed changes. One of the preferred indicators is phenology, the science of natural recurring events, as their recorded dates provide a high‐temporal resolution of ongoing changes. Thus, numerous analyses have demonstrated an earlier onset of spring events for mid and higher latitudes and a lengthening of the growing season. However, published single‐site or single‐species studies are particularly open to suspicion of being biased towards predominantly reporting climate change‐induced impacts. No comprehensive study or meta‐analysis has so far examined the possible lack of evidence for changes or shifts at sites where no temperature change is observed. We used an enormous systematic phenological network data set of more than 125 000 observational series of 542 plant and 19 animal species in 21 European countries (1971–2000). Our results showed that 78% of all leafing, flowering and fruiting records advanced (30% significantly) and only 3% were significantly delayed, whereas the signal of leaf colouring/fall is ambiguous. We conclude that previously published results of phenological changes were not biased by reporting or publication predisposition: the average advance of spring/summer was 2.5 days decade −1 in Europe. Our analysis of 254 mean national time series undoubtedly demonstrates that species' phenology is responsive to temperature of the preceding months (mean advance of spring/summer by 2.5 days°C −1 , delay of leaf colouring and fall by 1.0 day°C −1 ). The pattern of observed change in spring efficiently matches measured national warming across 19 European countries (correlation coefficient r =−0.69, P

Variations of the climatological growing season (1951–2000) in Germany compared with other countries - Annette Menzel; Gert Jakobi; Rein Ahas; Helfried Scheifinger; Nicole Estrella (International Journal of Climatology, 2003)
We analyse how variations in the climatological growing season, defined by single‐value thresholds of daily minimum and mean air temperature, mirror recent changes in plant phenological phases. In Germany (1951–2000, 41 climate stations), the dates of last spring frost T min A parallel evaluation of trends in the climatological growing season in other European countries (Austria, Switzerland, Estonia) supports this finding of a stronger lengthening of the frost‐free period than that of the growing season based on daily mean air temperature. The mean lengthening of the frost‐free period of 0.50 days per year in Austria and Switzerland (1951–99, 18 stations T mean ≥7 °C) in Austria and Switzerland (0.39 days per year) also approximates the respective result for Germany (0.36 days per year). However, in several cases, the trends increase with altitude (up to 500–900 m a.s.l.), but at high‐elevation climate stations (>950 m a.s.l.) weaker trends are again generally observed. Copyright © 2003 Royal Meteorological Society

Atmospheric mechanisms governing the spatial and temporal variability of phenological phases in central Europe - Helfried Scheifinger; Annette Menzel; Elisabeth Koch; Christian Peter; Rein Ahas (International Journal of Climatology, 2002)
A data set of 17 phenological phases from Germany, Austria, Switzerland and Slovenia spanning the time period from 1951 to 1998 has been made available for analysis together with a gridded temperature data set (1° × 1° grid) and the North Atlantic Oscillation (NAO) index time series. The disturbances of the westerlies constitute the main atmospheric source for the temporal variability of phenological events in Europe. The trend, the standard deviation and the discontinuity of the phenological time series at the end of the 1980s can, to a great extent, be explained by the NAO. A number of factors modulate the influence of the NAO in time and space. The seasonal northward shift of the westerlies overlaps with the sequence of phenological spring phases, thereby gradually reducing its influence on the temporal variability of phenological events with progression of spring (temporal loss of influence). This temporal process is reflected by a pronounced decrease in trend and standard deviation values and common variability with the NAO with increasing year‐day. The reduced influence of the NAO with increasing distance from the Atlantic coast is not only apparent in studies based on the data set of the International Phenological Gardens, but also in the data set of this study with a smaller spatial extent (large‐scale loss of influence). The common variance between phenological and NAO time series displays a discontinuous drop from the European Atlantic coast towards the Alps. On a local and regional scale, mountainous terrain reduces the influence of the large‐scale atmospheric flow from the Atlantic via a proposed ‘decoupling mechanism’. Valleys in mountainous terrain have the inclination to harbour temperature inversions over extended periods of time during the cold season, which isolate the valley climate from the large‐scale atmospheric flow at higher altitudes. Most phenological stations reside at valley bottoms and are thus largely decoupled in their temporal variability from the influence of the westerly flow regime (local‐scale loss of influence). This study corroborates an increasing number of similar investigations that find that vegetation does react in a sensitive way to variations of its atmospheric environment across various temporal and spatial scales. Copyright © 2002 Royal Meteorological Society.